AP3S1 is a Novel Prognostic Biomarker and Correlated With an Immunosuppressive Tumor Microenvironment in Pan-Cancer - Wu, Gujie; Chen, Mianxiong; Ren, Hefei; Sha, Xinyu; He, Min; Ren, Kuan; Qi, Juntao; Lin, Feng (Frontiers in Cell and Developmental Biology, 2022)
Background Adaptor-related protein complex 3, sigma 1 subunit(AP3S1) is one of the encoding subunits of the adaptor complex AP-3. However, its role in various tumor types and relationship with the tumor immune microenvironment (TIME) remains unclear. Methods AP3S1 expression was analyzed using datasets from The Cancer Genome Atlas, Genotype-Tissue Expression, UALCAN, and HPA databases. Then, we performed a systematic analysis of the genetic alterations, clinical features, and prognostic value of AP3S1 in pan-cancer. Gene set enrichment analysis (GSEA) and gene set variation analysis (GSVA) were used to identify the signaling pathways associated with AP3S1. The correlation between the level of immune cell infiltration and AP3S1 expression was analyzed using immune cell infiltration data from the ImmuCellAI， TIMER2, and a published study. Finally, we analyzed the association of AP3S1 with tumor mutational burden (TMB), microsatellite instability (MSI), and immune-related genes. Results AP3S1 was overexpressed in most tumors and significantly associated with low survival rates. GSEA and GSVA results show that AP3S1 is not only involved in tumor progression but is also associated with immune pathways in different tumor types. Then, we found that AP3S1 expression was positively correlated with the level of infiltration of immunosuppressive cells, such as tumor-associated macrophages and cancer-associated fibroblasts, and negatively correlated with NK and CD8+ T cells in pan-cancer. Expression of AP3S1 can affect TMB and MSI in a variety of cancers. In addition, AP3S1 levels positively correlate with most immunosuppressive genes such as PD-1, PD-L1, CTLA4, LAG3 and TIGIT in most cancer types. Conclusions Our study reveals that AP3S1 is a potential oncogene in pan-cancer. It plays an important role in tumorigenesis and cancer immunity, and elevated AP3S1 expression indicates an immunosuppressive microenvironment. Elevated expression of AP3S1 indicates an immunosuppressive microenvironment and can be used as a potential prognostic biomarker and a target for immunotherapy.